Working identity unconventional strategies for reinventing your career - Ibarra, Herminia, 1961- (Boston, Mass. : Harvard Business School Press, 2003)
Annotation Arguing that employees harbor a whole cast of "possible selves, " a Professor of Organizational Behavior at Harvard Business School advises readers to test possible futures when considering a career change.
Annotation.
Reinventing yourself -- Identity in transition. Possible selves. Between identities. Deep change -- Identity in practice. Crafting experiments. Shifting connections. Making sense -- Putting the unconventional strategies to work. Becoming yourself.
Includes bibliographical references (pages 183-192) and index.
Description based on print version record.
Keywords: Career changes; Career changes -- Psychological aspects; Self-actualization (Psychology); BUSINESS & ECONOMICS -- Careers -- Job Hunting; BUSINESS & ECONOMICS -- Careers -- Internships; Career changes; Career changes -- Psychological aspects; Self-actualization (Psychology); Loopbaanontwikkeling; elektronické knihy; electronic books